Bayesian Approach to "Healthy Worker Hire Effect" in Standardized Mortality Ratio Analysis. Issue 12 (December 2015) - Burstyn, Igor; Hamra, Ghassan B.; Symons, J. Morel
Abstract : Objectives: In this study, we address the healthy worker hire effect that arises when people with greater than average health are recruited to work in industrial jobs. Methods: Epidemiologists have used both general and working population reference rates to gauge influence of healthy worker hire effect on the standardized mortality ratio. We propose a Bayesian procedure that uses information derived from general and working population reference rates to calculate standardized mortality ratio. Results: The procedure is illustrated in the context of heart disease and lung cancer mortality analyses of a cohort of workers from a fluoropolymer production facility. Conclusions: Application of our method should allow for fuller discussions of the healthy worker effect when one of its components, the healthy worker hire effect, is evaluated quantitatively. Our method can be utilized to improve risk estimates for a cohort with occupational exposure. Abstract : Supplemental Digital Content is available in the text